Colorimetric susceptibility testing for Aspergillus fumigatus: comparison of menadione-augmented 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide and Alamar blue tests. - Jahn, B (1996)
Two colorimetric methods that use Alamar Blue or 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) for assaying the in vitro activities of antifungal agents have been described. We report that both tests performed similarly when the antifungal activity of amphotericin B against Candida albicans was determined. However, only the MTT test generated interpretable data when Aspergillus fumigatus was used.